Advancing Transcranial Magnetic Stimulation Methods for Complex Regional Pain Syndrome: An Open‐Label Study of Paired Theta Burst and High‐Frequency Stimulation. Issue 4 (4th March 2018) - Gaertner, Mark; Kong, Jiang‐Ti; Scherrer, Kristen H.; Foote, Alyssa; Mackey, Sean; Johnson, Kevin A.
Abstract : Introduction: Complex Regional Pain Syndrome (CRPS), a rare and severe chronic pain condition, often responds poorly to existing treatments. Previous studies demonstrated Transcranial Magnetic Stimulation (TMS) provided short‐term pain relief for upper extremity CRPS. Methods: Building on previous methodologies, we employed a TMS protocol that may lead to significant pain relief for upper and lower extremity CRPS in a nonrandomized open label pilot trial involving 21 participants. We individualized TMS coil positioning over motor cortex of somatic pain location, and administered intermittent theta‐burst stimulation followed by 10 Hz high‐frequency stimulation using a deeper targeting coil. We assessed response (≥30% pain reduction) from a single session ( n = 5) and five consecutive daily sessions ( n = 12) and compared change in pain from baseline, after one treatment and one‐week posttreatment between groups using a mixed ANVOA. Results: Both groups demonstrated significant pain reduction after one session and one‐week posttreatment; however, no group differences were present. From a single session, 60% of participants responded at Week 1. From five sessions, 58% and 50% of participants responded at Weeks 1 and 2, respectively. Two from each group achieved >50% pain reduction beyond six to eight weeks. No serious adverse events occurred. Though headache and nausea were the most common side‐effects, we urge careful monitoring to prevent seizures with this protocol. Conclusions: We used a TMS protocol that, for the first time, led to significant pain relief in upper and lower extremity CRPS, and will soon examine our protocol in a larger, controlled trial.